2018
DOI: 10.2478/rrlm-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

Is galectin-3 a promoter of ventricular dysfunction?

Abstract: Heart failure is nowadays a common condition associated with high mortality and increased healthcare-related

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…The detailed information about the role of galectin-3 in mediation of inflammation by different pathways is presented in an extensive review by Lupu et al In this review the clinical utility of the detection of this biomarker is provided. (9) Another important tool involved in progression of chronic HF, oxidative stress and inflammation, was investigated by Iliesiu et al The objective of this study was to evaluate the association between seric uric acid, oxidative stress and inflammation markers in patients with moderate-severe HF reduced left ventricular ejection fraction. It was shown that elevated level of uric acid is correlated with disease severity and in the absence of renal failure may mirror increased xanthine-oxidase activity associated with chronic inflammatory response.…”
Section: Biomarkers Beyond Clinical Utilitymentioning
confidence: 99%
“…The detailed information about the role of galectin-3 in mediation of inflammation by different pathways is presented in an extensive review by Lupu et al In this review the clinical utility of the detection of this biomarker is provided. (9) Another important tool involved in progression of chronic HF, oxidative stress and inflammation, was investigated by Iliesiu et al The objective of this study was to evaluate the association between seric uric acid, oxidative stress and inflammation markers in patients with moderate-severe HF reduced left ventricular ejection fraction. It was shown that elevated level of uric acid is correlated with disease severity and in the absence of renal failure may mirror increased xanthine-oxidase activity associated with chronic inflammatory response.…”
Section: Biomarkers Beyond Clinical Utilitymentioning
confidence: 99%
“…According to Kubanek M. et al [17] galectin-3 plays an important role in the initial stages of heart failure formation and is an important predictor of left ventricular hypertrophy. One of the certain limitations in estimating the prognostic value of galectin-3 is the dependence on sexual and age-related differences, as well as on the size of renal glomerular filtration [19].…”
Section: Introductionmentioning
confidence: 99%